Condyloma and coincidental epidermodysplasia verruciformis acanthoma positive for human papillomavirus‐14 and ‐21. (14th September 2022) - Bartley, Brooke; Cho, Woo Cheal; Rady, Peter L.; Dai, Julia; Curry, Jonathan L.; Milbourne, Andrea; Tyring, Stephen K.; Torres‐Cabala, Carlos A.
Abstract: Epidermodysplasia verruciformis (EDV) is a rare genodermatosis that predisposes individuals to persistent infection with β‐human papillomavirus (HPV) genotypes. The term EDV acanthoma may be applied to lesions with incidental findings of EDV‐defining histopathological features without clinical signs of EDV. We report a case of HPV‐14‐ and ‐21‐positive EDV acanthoma arising in association with condyloma in a female patient with a history of low‐grade squamous intraepithelial lesion of the cervix positive for high‐risk HPV (non‐16/18), chronic kidney disease, and systemic lupus erythematosus. The patient had no family or personal history of EDV, but the patient was on immunosuppressive therapy with mycophenolate mofetil and prednisone. A biopsy specimen from one of the perianal lesions revealed histopathologic changes consistent with EDV in the setting of condyloma. Molecular testing showed HPV‐14 and ‐21, which supported the coexistence of condyloma with EDV acanthoma.